2000
DOI: 10.1002/(sici)1098-2795(200003)55:3<335::aid-mrd12>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of onset of mouse sperm acrosome reaction induced by solubilized zona pellucida: Fluorimetric determination of loss of pH gradient between acrosomal lumen and medium monitored by dapoxyl (2-aminoethyl) sulfonamide and of intracellular Ca2+ changes monitored by Fluo-3

Abstract: The onset of the zona pellucida-induced acrosome reaction in mouse sperm is marked by loss of the pH gradient existing in acrosome-intact sperm between the acidic acrosomal lumen and the suspending medium, due to pore formation between outer acrosomal and plasma membranes. In earlier work, it was shown that this pH gradient loss occurred in single sperm bound to structurally intact zonae pellucidae with a half-time of 2.1 min; the extended kinetics of this loss determined in a sperm population bound to intact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These values fall in the range of previously described ZP‐induced kinetics. Indeed, a wide range of ZP‐induced calcium increase kinetics have been reported in the past and peaks were reached from few seconds (Shirakawa and Miyazaki, 1999; Rockwell and Storey, 2000; Fukami et al, 2003) to minutes (Arnoult et al, 1996; Fukami et al, 2003). This range is likely due to experimental differences between groups, like ZP concentration, capacitation time or medium composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values fall in the range of previously described ZP‐induced kinetics. Indeed, a wide range of ZP‐induced calcium increase kinetics have been reported in the past and peaks were reached from few seconds (Shirakawa and Miyazaki, 1999; Rockwell and Storey, 2000; Fukami et al, 2003) to minutes (Arnoult et al, 1996; Fukami et al, 2003). This range is likely due to experimental differences between groups, like ZP concentration, capacitation time or medium composition.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments were carried out at 37°C in a continuous flow of medium. Solubilized zona pellucida, prepared as precisely described (Rockwell and Storey, 2000), was introduced in the recording medium by adding 10 µl of a solution containing 20 solubilized ZP by µl (final volume 100 µl). Thus, the final solubilized ZP concentration is 2 ZP/µl.…”
Section: Methodsmentioning
confidence: 99%
“…Using spectrofluorimetry, we found that the calcium response to hZP may be biphasic or monophasic, depending on the sample. Previous studies using spectrofluorimetry and a similar probe showed that the Ca 2+ response to solubilised mouse ZP [33] or recombinant hZP3 [5,6] was biphasic, with a first transient peak and a second sustained phase. However, in nine of the 21 cases analysed in our study, the calcium response appeared to be monophasic, with only sustained increase in calcium concentration.…”
Section: Discussionmentioning
confidence: 99%